Handbook on innovation, society and the environment - Díaz López, Fernando J.; Mazzanti, Massimiliano; Zoboli, Roberto (Elgar handbooks in energy, the environment and climate change, 2023)
"Through careful investigation into the role of eco-innovation as a catalysing factor in the societal transition towards sustainability, this Handbook proposes more appropriate measures of innovation as a driver of change. It examines innovation from various perspectives, including labour, trade, the circular economy and energy, to illustrate a more comprehensive picture of its impacts. Chapters by leading authors from the sectors of eco-innovation, sustainability transformations and green and circular economies provide a meticulously balanced observation of innovation at local, regional, national and global scales. By featuring case studies from across Australasia, Europe and Latin America, as well as empirical work and modelling exercises, this forward-thinking Handbook links innovation to a range of interconnected topics. It imparts new evidence to offer a succinct conclusion about the potential success of certain innovation and green industrial policies. This enlightening Handbook will be valuable for scholars and academics studying economics and management, economic and social innovation, and environmental policy. It will also be of great benefit for those analysing policy and industry professionals looking to learn more about eco-innovation."